Risk Associated with Management of Engineering Projects Using Intelligent Based Control System (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Some abandoned Engineering projects observed in some parts of the country this present era has arisen as a result of these factors Scope Creep, Schedule Delays, Budget Overruns, Safety Hazards, Technical Challenges and Additional Risk Factors. This is surmounted by introducing reducing risk associated with management of engineering projects using intelligent based control system. To achieve this, it was done in this manner, characterizing and establishing the causes of the risk associated with management of engineering projects, designing a conventional SIMULINK model for the risk associated with management of engineering projects, designing management rule base that will reduce the percentage of the risk associated with management of engineering projects, training ANN in the management rule base to enhance the efficacy of reducing the percentage of the risk associated with management of engineering projects, developing an algorithm that will implement the process, designing a SIMULINK model for reducing risk associated with management of engineering projects using intelligent based control system and validating and justifying the percentage improvement in the reduction of risk associated with management of engineering projects with and without intelligent based control system. The results obtained are the conventional Scope Creep that caused risk associated with management of engineering project was12%. On the other hand, when an intelligent based control system was introduced in the system, the percentage of risk observed in management of engineering project was reduced to10.4%, the conventional Safety Hazards that caused high risk associated with management of engineering projects was7%. However, when an intelligent based control system was integrated in the system the risk associated with management of engineering projects reduced to6.07% and the conventional Additional Risk Factors that caused risk associated with management of engineering projects was32% while when an intelligent based control system was imbibed in the system, it wittingly reduced to27.75%. Finally, with these results obtained, it shows that the percentage improvement in the reduction of risk associated with management of engineering projects when an intelligent based control system was integrated in the system over the conventional competitor was 4.25%.